Plasma Protein Signatures of a Murine Venous Thrombosis Model and Slc44a2 Knockout Mice Using Quantitative-Targeted Proteomics - Tilburg, Julia; Michaud, Sarah A.; Maracle, Chrissta X.; Versteeg, Henri H.; Borchers, Christoph H.; van Vlijmen, Bart J. M.; Mohammed, Yassene (Thrombosis and Haemostasis, 2020)
The plasma compartment of the blood holds important information on the risk to develop cardiovascular diseases such as venous thrombosis (VT). Mass spectrometry-based targeted proteomics with internal standards quantifies proteins in multiplex allowing generation of signatures associated with a disease or a condition. Here, to demonstrate the method, we investigate the plasma protein signatures in mice following the onset of VT, which was induced by RNA interference targeting the natural anticoagulants antithrombin and protein C. We then study mice lacking Slc44a2, which was recently characterized as a VT-susceptibility gene in human genome-wide association studies. We use a recently developed panel of 375 multiplexed mouse protein assays measured by mass spectrometry. A strong plasma protein siganture was observed when VT was induced. Discriminators included acute phase response proteins, and proteins related to erythrocyte function. In mice lacking Slc44a2, protein signature was primarily overruled by the difference between sexes and not by the absent gene. Upon separate analyses for males and females, we were able to establish a signature for Slc44a2 deficiency, in which glycosylation-dependent cell adhesion molecule-1 and thrombospondin-1 were shared by both sexes. The minimal impact of Slc44a2 deficiency on the measured plasma proteins suggests that the main effect of Slc44a2 on VT does not lay ultimately in the plasma compartment. This suggests further investigation into the role of this VT-susceptibility gene should perhaps also question the possible involvement in cellular mechanisms.
Keywords: proteomics; venous thrombosis; experimental animal model; blood proteins; SLC44A2 protein